Nurses’ attitudes and knowledge regarding patient rights: a systematic review - Mpouzika, Meropi; Karanikola, Maria; Panayiotou, Elena; Raftopoulos, Vasilios; Middleton, Nicos; Papathanassoglou, Elizabeth (Revista da Escola de Enfermagem da USP, 2021)
Objective: To synthesize current evidence on nurses' attitudes and/or knowledge on the entire spectrum of patient rights. Method: A systematic search of the literature was performed in Web of Science, PubMed, Scopus and CINAHL. Studies were selected according to pre-defined inclusion/exclusion criteria. The Cochrane and PRISMA guidelines, including templates for systematic reviews, were applied. For rigor assessment, the Critical Appraisal Skills Program Qualitative Research Checklist, and the Center for Evidence-Based Management tool were employed. Results: Thirteen studies were included, that exhibited important methodological limitations, such as convenience sampling, mediocre response rates and inadequate instrument validity. Findings indicated: a) low level of awareness regarding patient rights among nurses, b) knowledge discrepancies on specific aspects of patient rights, c) low priority ascribed to a patient's right to access information, and d) insufficient evidence on formal educational sources of knowledge on the topic of patient rights. Conclusion: Narrow geographical localization, heterogeneity and methodological limitations render generalizability of the conclusions difficult. Further research based on robust methodology is proposed.